Development of Textbook: Mental Health Flipbook for Guidance and Counselling Student in Higher Education - Puriani, Risma Anita; Dewi, Ratna Sari; Lubis, Khadijah; Marlini, Leny; Pratama, Nanda Putra (Bulletin of Counseling and Psychotherapy, 2025)
Textbooks are one of the media specifically designed to assist the learning process in a particular subject area. Textbooks have an important function, books that are used as handbooks for courses compiled and written by experts in their fields. Through textbooks, students are expected to be able to obtain information and various activity instructions in learning in each course. This study aims to develop Flipbook Teaching Materials in Mental Health Courses for Guidance and Counselling students of FKIP Sriwijaya University. Measurements in this study on the main data, namely the results of coursebook assessments on media validation, material validation, and language validation, as well as the results of the flipbook feasibility test by measuring student absorption of the material in the coursebook. This research uses the ADDIE development method with a series of Analysis, Design, Development, Implementation and Evaluation. the instruments in this study were expert validation sheets and respondent rating scales. The results showed media validation with a total average of 4.43 with the category "very feasible", material aspects total average of 4.7 with the category "very feasible", and validation of language aspects total average of 4.66 categorised as "very feasible". While the Flipbook effectiveness score with a respondent rating scale of 42 students. At the One to one stage, the N-Gain value was obtained at 0.786 with a percentage of 78.57% with the effective category, then at the Small Group stage, the N-Gain value was obtained at 0.766 with a percentage of 76.61% with the effective category and at the Field test stage, the N-Gain value was obtained at 0.767 with a percentage of 76.70% with the effective category. Thus it can be concluded that the Mental Health flipbook is effective for use in Mental Health courses. Based on these findings, it can be concluded that the textbook with the title "Development of Flipbook Teaching Materials in Mental Health Courses for Students of the Guidance and Counselling Study Program at FKIP Sriwijaya University" is effectively used in learning Mental Health courses and achieving competencies according to the course learning outcomes planned in the Semester Learning Plan (RPS).